Analisis Penggunaan Bahasa Indonesia dalam Makalah Pendidikan Jasmani Kesehatan dan Rekreasi - Ika Febriana; Ariel Ginting; Fifi Vellina Berutu; Remika Maretama Situmorang; Sasta Syehan Yadaini (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to analyze the use of Indonesian in the Physical Education, Health and Recreation study program. Investigate how to use Indonesian language and language styles effectively and support data collection in writing papers in the Physical Education, Health and Recreation study program. This research uses a qualitative approach to investigate a series of academic papers and analyze the conformity of Indonesian language use with academic conventions and scientific language characteristics. The research results show that there are differences in language style and use of terminology, the majority of papers are able to meet relevant academic standards, although there are still obstacles in translating technical terms and using terminology consistently. This research can help academic writers to further refine the use of Indonesian in writing work in the Health and Recreation Services Education study program.